Changes of the acute myocardial infarction-related resident deaths in a transitioning region: a real-world study involving 3.17 million people - Zhao, Yajun; Zou, Jian; Chen, Yichen; Zhou, Jing; Dai, Wei; Peng, Minghui; Li, Xiaopan; Jiang, Sunfang (Frontiers in Public Health, 2023)
Background: The impact of acute myocardial infarction (AMI) on the life span of residents in a transitioning region has not been studied in depth. Therefore, we aimed to evaluate the changes in AMI-related resident deaths in a transitioning region in China. Methods: A longitudinal, population-based study was performed to analyze the deaths with/of AMI in Pudong New Area (PNA),Shanghai from 2005 to 2021. The average annual percentage change (AAPC) of AMI in crude mortality rates (CMR), age-standardized mortality rates worldwide (ASMRW), and rates of years of life lost (YLLr) were calculated by the joinpoint regression. The impact of demographic and non-demographic factors on the mortality of residents who died with/of AMI was quantitatively analyzed by the decomposition method. Results: In 7,353 residents who died with AMI, 91.74%(6,746) of them were died of AMI from 2005 to 2021. In this period, the CMR and ASMRW of residents died with/of AMI were 15.23/105 and 5.17/105 person-years, the AAPC of CMR was 0.01%(95% CI: -0.71,0.72, P=0.989) and 0.06%(95% CI: -0.71,0.84, P=0.868), and the ASMRW decreased by 2.83%(95% CI: -3.66,-2.00, P<0.001) and 2.76%(95% CI: -3.56,-1.95, P<0.001), respectively; The CMR of people died of AMI showed a downward trend(all P<0.05) in people ≥60 years but an upward trend(AAPC=2.47%(95% CI: 0.07,4.94, P=0.045)) in people of 45-59 years; The change in CMR of people died with/of AMI caused by demographic factors was 28.70%(95% CI: 12.99,46.60, P=0.001) and 28.07%(95% CI: 12.71,45.52, P=0.001) per year, respectively. Conclusions: Preventative strategies for AMI should be applied to enhance the health management of residents aged 45-59 years or with comorbidities in the transitioning region.